Pengaruh Pemberian Posisi Pronasi dan Nesting Terhadap Peningkatan Saturasi Oksigen pada Bayi dengan Asfiksia Sedang di Ruang NICU RSUD Temanggung - Ramadhani Dewi Cahyaningrum; Ferika Indarwati; Layli Anisah (Sci-tech Journal, 2025)
Premature birth and birth complications such as asphyxia remain a major cause of neonatal death in Indonesia. Interventions such as pronation positioning and nesting techniques have been shown to improve oxygenation and respiratory function in neonates. Pronation positioning, which reduces abdominal compression, and the application of nesting techniques that mimic the conditions of the womb, show significant results in stabilizing the respiration and oxygenation of newborns with asphyxia. Studies show that positional changes can reduce shortness of breath and increase oxygen saturation, supporting optimal care for premature infants. This study used a case report with the intervention of providing pronation positioning and nesting in asphyxiated infants in the NICU. The intervention was carried out for five consecutive days with a duration of 2 hours per day. Case Study Results: This case study shows that after being given pronation positioning and nesting, there was a change in oxygen saturation on the first day from 88% to 90% and on the fifth day there was a change in oxygen saturation from 98% to 100%. Conclusion: Pronation positioning and nesting have a positive effect on increasing oxygen saturation in patients with asphyxia.